Assessing risk of self-harm in acute paediatric settings: a multicentre exploratory evaluation of the CYP-MH SAPhE instrument. Issue 5 (28th May 2021) - Manning, Joseph C; Carter, Tim; Walker, Gemma; Coad, Jane; Aubeeluck, Aimee
Abstract : Objective: To psychometrically assess the Children and Young People-Mental Health Self-harm Assessment in Paediatric healthcare Environments (CYP-MH SAPhE) instrument for the identification of immediate risk of self-harm in CYP, aged 10–19 years, in acute paediatric wards or emergency departments. Design: The CYP-MH SAPhE Instrument was developed through a robust scoping review and Delphi consensus with 30 clinicians/topic experts. To evaluate the psychometric properties, a multicentre exploratory study was conducted. Setting: Three acute hospitals in the UK. Participants: 163 CYP presenting at acute hospital settings with primary mental health (cases) or physical health (non-cases) conditions. Primary and secondary outcome measures: Psychometric properties of the CYP-MH SAPhE instrument were evaluated through Principle Axis Factoring (PAF) with Oblimin (Kaiser normalisation) alongside measures of internal consistency (Cronbach's α), convergent, discriminant and face validity. Results: PAF of the dichotomous items (n=9) loaded onto three factors (1) behaviours and intentions; (2) suicidality and (3) self-harm. Factors 1 (Cronbach's α=0.960) and 3 (Cronbach's α=1) had high internal consistency. There was: good level of agreement between raters (kappa=0.65); a moderately positive correlation between the CYP-MH SAPhE instrument and the Columbia-Suicide Severity Rating Scale; and discrimination between cases and non-cases across the three factors (factor 1: m=88 vs 70; factor 2: m=102 vs 70; factor 3: m=104 vs 68). Assessment of face validity resulted in six items being removed, culminating in an eight question, rapid assessment instrument. Conclusions: The results support the CYP-MH SAPhE Tool as a potentially reliable and valid instrument to identify immediate risk of self-harm in CYP presenting to acute paediatric healthcare environments, which is a burgeoning and significant global health issue.